Analysis of Public Environmental Expenditure : The Case Study of Jakarta Province - Putra, Didi Prabowo; Edward, James Thomas (UI Scholars Hub, 2023)
The national struggle for sustainable development influenced the sub-national governments level in composing their policy directions especially public budget policy. Nonetheless, although the environmental protection function is important, it tends to be marginalized in the national budgetary debates. This study, therefore, attempts to analyse the ‘green budget’ allocation and utilization within the Regional Medium-term Development Plan 2013 – 2017 of Jakarta Province. The methodology draws on descriptive analysis of derived data from annual provincial budget documents, and in-depth interview analysis explored potential barriers and drivers give rise to gaps in budget between the allocation and realization stage. Results show that the allocated ‘green budget’ posture of Jakarta Province was 6.1% in the five years average, significantly higher when compared to the national level at 0.8 – 1 percent. However, the realization was low with average actual spending at 47.1% of the total allocated budget. The interviews point to the collaboration aspect among the profound drivers to support environmental affairs policy. Meanwhile, the aspects of staff capacity, public awareness, and policy alignment are believed to be significant barriers that the government is recommended to take into consideration.